The relationship between acculturation and mental health of 1st generation immigrant youth in a representative school survey: does gender matter? - Eva M. Klein; Kai W. Müller; Klaus Wölfling; Michael Dreier; Mareike Ernst; Manfred E. Beutel (BMC, 2020)
Abstract Background Although gender plays a pivotal role in the psychological adaptation of immigrant youth, its association with acculturation strategy and mental health among 1st generation immigrant adolescents are still scarce and inconsistent. Therefore, the purpose of the current study was to investigate gender-related differences in acculturation patterns and their association with mental health (internalizing and externalizing problems). Methods Self-reported data of immigrant adolescents (N = 440) aged between 12 and 19 years (M = 16.2; SD = 1.6) was collected in a representative German school survey. Fifty-one percent of the sample were female (n = 224). Almost half of the sample was born in the Former Soviet Union, followed by Poland (9.3%). Sociodemographic variables, acculturation strategies, and internalizing as well as externalizing problems were assessed by questionnaires. Results Confirmatory factor analysis supported the four- dimensional model of acculturation styles (assimilation, integration, separation and marginalization). Whereas girls more often showed an integration pattern, boys scored higher on the separation and marginalization scale. After adjusting for age and educational level, regression analyses revealed for both gender that marginalization was associated with more internalizing problems. Separation was related to more externalizing problems. Conclusion 1st generation adolescents experiencing a lack of belongingness to German society, socio-economic and educational disadvantages might be particularly vulnerable to mental distress. Findings are discussed in terms of gender-related differential socialization processes in context of immigration.